Di-[trioctyl-(8-phenyloctyl)-phosphonium] pamoate: synthesis and characterization of a novel, highly hydrophobic ionic liquid for the extraction of scandium, thorium and uranium - Gradwohl, Andreas; Windisch, Jakob; Rosner, Alexander; Heninger, Julia; Fuhrmann, Philipp L.; Wallner, Gabriele; Keppler, Bernhard K.; Kandioller, Wolfgang; Jirsa, Franz (Frontiers in Chemistry, 2024)
We synthesized and characterized a novel, task-specific ionic liquid for metal extraction with considerably reduced leaching behavior compared to similar, phosphonium-based ionic liquids. The synthesis involves the design of the novel compound [TOPP]2[PAM] featuring both a highly hydrophobic cation and a functional anion. The characterization of the novel ionic liquid confirmed the formation of the desired structure and sufficient purity. The high viscosity of [TOPP]2[PAM] is responsible for the comparably high working temperature of 50°C. Extraction experiments demonstrated the suitability of [TOPP]2[PAM] for extracting Sc, Th and U from aqueous matrices, whereby extraction efficacies of 87.3 ± 9.1 % (Sc), 95.8 ± 2.3 % (Th) and 92.7 ± 0.3 % (U) were achieved over 24 hours. Furthermore, Sc could be separated to a high degree via selective extraction from Th as well as from the rare earth elements Y, La, Ce, Nd, Eu, Ho and Lu. Th was separated from La, Ce, Nd, Eu, Ho and Lu at pH 1.00. During all extraction experiments, leaching into the aqueous extraction matrix peaked at only 0.134 ± 0.011 % after 24 hours. The loading capacities for [TOPP]2[PAM] differed between the investigated metals, the highest values being achieved for U. After extraction, 82.7 ± 2.8 % of the extracted Sc could be recovered from the IL using nitric acid (10 %), but less of Th and U.